2014
DOI: 10.1186/1746-6148-10-2
|View full text |Cite
|
Sign up to set email alerts
|

Resiquimod and polyinosinic–polycytidylic acid formulation with aluminum hydroxide as an adjuvant for foot-and-mouth disease vaccine

Abstract: BackgroundToll-like receptor (TLR) agonists reportedly have potent antiviral and antitumor activities and may be a new kind of adjuvant for enhancing immune efficacy. Resiquimod (R848) is an imidazoquinoline compound with potent antiviral activity and functions through the TLR7/TLR8 MyD88-dependent signaling pathway. Polyinosinic-polycytidylic acid [poly(I:C)] is a synthetic analog of double-stranded RNA that induces the production of pro-inflammatory cytokines by the activation of NF-κB through TLR3. This stu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
15
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(16 citation statements)
references
References 26 publications
1
15
0
Order By: Relevance
“…Previous research demonstrated that Poly I:C can reduce the replication of Chikungunya virus in vitro [39] and pretreatment of mice with poly I:C provided significant protection against SARS and influenza infection [40]. Poly I:C was also effective as an adjuvant for Foot and Mouth disease vaccine in pigs [23,41] and for influenza virus vaccine studies in chickens [42,43]. In humans, efficacy and safety of Ampligen (synthetic poly I:C) are being tested in clinical experiments.…”
Section: Discussionmentioning
confidence: 99%
“…Previous research demonstrated that Poly I:C can reduce the replication of Chikungunya virus in vitro [39] and pretreatment of mice with poly I:C provided significant protection against SARS and influenza infection [40]. Poly I:C was also effective as an adjuvant for Foot and Mouth disease vaccine in pigs [23,41] and for influenza virus vaccine studies in chickens [42,43]. In humans, efficacy and safety of Ampligen (synthetic poly I:C) are being tested in clinical experiments.…”
Section: Discussionmentioning
confidence: 99%
“…Combining adjuvants could be as beneficial as the tailoring of the response, and several publications have shown synergistic effects. Plant‐derived adjuvants, in this case rapeseed oil and ginseng saponins (Zhang et al., ), and the synthetic TLR7/8 ligand R848 and poly I:C combined with a traditional aluminium hydroxide‐adjuvanted vaccine (Zhou et al., ), have shown promise. An oil/gel combination (ISA 201, Carbigen, Emulsigen‐D) also induced improved immunity compared to traditional vaccines in pigs.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Zhou et al . (2014) reported that mice immunized with TLR7 ligands showed a markedly enhanced resistance to FMDV 30 . Kato et al .…”
Section: Discussionmentioning
confidence: 99%